Optimalisasi kandungan gizi cookies berbahan dasar ikan gabus dan jagung sebagai makanan tambahan untuk menanggulangi stunting pada balita - Febry, Fatmalina; Flora, Rostika; Bingsih, Windi Indah Fajar (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Handling nutritional problems for toddlers can be done by diversifying the development of additional food formulas by considering nutritional aspects. Nutrient-dense additional food is one effort to fulfill the nutritional intake of toddlers. Snakehead fish flour and corn flour cookies have quite high nutritional content which is expected to be an alternative additional food for toddlers.Objectives: This research aims to analyze the proximate content of snakehead fish flour and corn flour cookies and compare it with quality standards for toddler supplementary food.Methods: Descriptive research using an experimental design. The cookies were made at the Culinary and Dietetics Laboratory of the Faculty of Public Health, Sriwijaya University, and the proximate content testing was carried out at the Chem-Mix Pratama Laboratory in Yogyakarta from September to November 2023. The subjects of this study were 2 (two) cookie formulas, namely F3 (treatment) and F4 (control). The results of the analysis of the proximate content of cookies were compared with SNI 01-2973-2011 and Permenkes No. 51 of 2016 regarding the quality standards of supplementary food for toddlers. Data were analyzed descriptively using the average and deviation calculations.Results: There is an increase in proximate levels of protein, fat, water, and ash in F3 cookies after being substituted with cork fish flour and corn flour. The proximate content of F3 cookies has met the standards of SNI 01-2973-2011 and Permenkes No. 51 of 2016, namely energy, carbohydrates, fat, and protein. The water and ash content has not met these standards.Conclusion: Snakehead fish flour and corn flour cookies meet the nutritional requirements for supplementary food for toddlers.